In Vivo Studies Exploring the Impact of IUGR in Rat Models on Offspring Malnutrition: A Systematic Review - Sukandar, Umar Gunarsa; Prasetyorini, Nugrahanti (Asian Journal of Health Research, 2024)
Introduction: Intrauterine growth restriction (IUGR), stemming from inadequate fetal nutrition due to maternal or placental factors, affects 10–15% of pregnancies worldwide. Animal models reflect human IUGR, showing malnutrition-associated outcomes like impaired growth, reduced body weight, delayed puberty, and disruptions in genetic and hormonal processes. Despite extensive research, gaps persist in understanding how IUGR impacts fetal outcomes, particularly regarding malnutrition-related outcomes. Material and Methods: The literature search was conducted in four databases. Several outcomes were analyzed, including the timing of puberty, weight and body composition, and organ development, which represented the IUGR rat's malnutrition condition. Throughout the identification process, 11 articles were included in the systematic review. Results: Research consistently demonstrates that IUGR in rat models results in delayed puberty, characterized by delayed vaginal opening and lower body weights compared to controls across early and later developmental stages. Additionally, IUGR adversely affects organ development, with studies showing reduced brain weights, diminished ovarian and mammary gland development, and altered sizes of reproductive organs. Furthermore, IUGR disrupts hormonal and genetic profiles, as evidenced by changes in ovarian follicle counts, altered gene expressions related to testicular development, and dysregulated metabolic pathways. All malnutrition-related outcomes significantly differed between IUGR and control rats (p < 0.05). Conclusion: IUGR in rat models consistently induces developmental delays and physiological impairments in offspring, characterized by delayed puberty, reduced body weights, and compromised organ development, highlighting the adverse consequences of malnutrition associated with IUGR.